Assessment of TiO₂–C-dots Nanocomposites Derived from Tofu Liquid Waste for Post-Mining Soil Remediation: Its Application in Bengkulu Province - Jhon Lucky Silalahi; Mokhammad Khatami (Reaktor, 2026)
This paper critically evaluates the technological feasibility of producing TiO₂–carbon dots (C-dots) nanocomposites from tofu liquid waste as a biomass-derived carbon precursor for soil remediation in a post-mining environment. Rather than assuming conversion efficiency or economic viability, the analysis is structured around the synthesis routes, composite fabrication strategies, and process–structure–performance relationships curated from the relevant literature. Biomass-to-C-dots conversion pathways, including hydrothermal, microwave-assisted, and pyrolytic methods, are assessed with respect to feedstock tolerance, operational conditions, and product characteristics. Integration strategies between C-dots and TiO₂, namely in situ growth, impregnation, and sol–gel hybridization, are assayed in terms of their interfacial coupling, stability, and photocatalytic relevance for heavy-metal immobilization. A regional case context from Bengkulu Province is used solely to illustrate feedstock availability and chemical relevance, without extrapolating to production yield or economic feasibility. The results demonstrate that the functional performance of TiO₂–C-dots systems is governed primarily by synthesis parameters and composite architecture rather than by precursor volume. Current evidence situates this technology at an early development stage, where reproducible fabrication and interfacial engineering remain the principal determinants of applicability. These findings provide a process-centered framework for evaluating biomass-derived photocatalytic composites while avoiding premature feasibility claims unsupported by mature conversion technologies.